Correlation of hypoxemia with clinical signs in children aged 2 months to 5 years with acute lower respiratory tract infection: a prospective observational study - Mehta, Niyati; Muley, Prasad; Badhiye, Ankita; Lawande, Vikrant (International Journal of Contemporary Pediatrics, 2026)
Background: Acute lower respiratory tract infection (LRTI), particularly pneumonia, is a leading cause of morbidity and mortality in children under five years of age globally. Hypoxemia is a major complication and risk factor for death in these patients. This study aimed to correlate hypoxemia with clinical signs, laboratory markers and outcomes in children with acute LRTI. Methods: A prospective observational study was conducted in the pediatric intensive care unit (PICU) of a tertiary care hospital Dhiraj Hospital Piparia. The study enrolled 61 children aged 2 months to 5 years diagnosed with WHO-defined community-acquired pneumonia. Clinical signs, anthropometry, laboratory parameters (CBC, CRP) and chest X-rays were recorded. Oxygen saturation (SpO2) was monitored every 6 hours. Hypoxemia was defined as SpO2 ≤ 90%. Statistical analysis was performed to determine associations between hypoxemia and clinical variables. Results: Of 61 patients, 59.02% (36/61) presented with hypoxemia. The majority were infants (75.41%) and males (73.77%). Hypoxemia was significantly associated with nasal flaring (p=0.022), chest indrawing (p=0.011) and the combination of both (p=0.001). All patients presenting with cyanosis (100%) were hypoxemic. Radiological consolidation was significantly associated with lower SpO2 (p=0.003), as were elevated total leukocyte counts (p=0.029) and C-reactive protein levels (p=0.006). Longer duration of oxygen support was required in hypoxemic patients (p=0.012). No significant association was found between hypoxemia and age, gender, nutritional status, severity of anemia or severity of pneumonia classification. Conclusions: Clinical signs such as nasal flaring, chest indrawing and cyanosis are reliable bedside predictors of hypoxemia in children with LRTI. While pulse oximetry remains the gold sta